Plastic Ingestion in Post-hatchling Sea Turtles: Assessing a Major Threat in Florida Near Shore Waters - Eastman, Catherine B.; Farrell, Jessica A.; Whitmore, Liam; Rollinson Ramia, Devon R.; Thomas, Rachel S.; Prine, Jenifer; Eastman, Scott F.; Osborne, Todd Z.; Martindale, Mark Q.; Duffy, David J. (Frontiers in Marine Science, 2020)
Pollution from anthropogenic marine debris, particularly buoyant plastics, is ubiquitous across marine ecosystems. Due to the persistent nature of plastics in the environment, their buoyancy characteristics, degradation dynamics, and ability to mimic the behavior of natural prey, there exists significant opportunity for marine organisms to ingest these man-made materials. In this study we examined gastrointestinal (GI) tracts of 42 post-hatchling loggerhead (Caretta caretta) sea turtles stranded in Northeast Florida. Necropsies revealed abundant numbers of plastic fragments ranging from 0.36 mm to 12.39 mm in size (length), recovered from the GI tracts of 39 of the 42 animals (92.86%), with GI burdens ranging from 0-287 fragments with a mass of up to 0.33 g per turtle. Post-hatchlings weighed from 16.0-47.59 g yielding a plastic to body weight percentage of up to 1.23%. Several types of plastic fragments were isolated, but hard fragments and sheet plastic were the most common type, while the dominant frequency of fragment color was white. Fragment size and abundance mixed with natural gut contents suggests significant negative health consequences from ingestion in animals at this life stage. Gaining greater insight into the prevalence of plastic ingestion, the types of plastic and the physiological effects of plastic consumption by multiple life-stages of sea turtles will aid the prioritization of mitigation efforts for the growing marine debris problem. This report demonstrates that plastic ingestion is a critical issue for marine turtles from the earliest stages of life.